2015
DOI: 10.1097/ss.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Properties at Farm Scale Using a Model-Based Soil Sampling Scheme and Random Forest

Abstract: Digital soil mapping techniques can reduce the costs associated with improving soil information at the farm scale. Many techniques exist for generating a digital soil mapping. In this study, we tested the use of a random forest (RF) and two model-based soil-sampling scheme, conditioned with Latin hypercube (cLHS) and fuzzy c-means sampling (FCMS) to predict soil properties for a 68-ha agricultural field. The predictor set included the use of inexpensive auxiliary information such as digital elevation models, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In our case studies, SRS and cLHS were equivalent in terms of map accuracy. Several studies (e.g., Castro‐Franco, Costa, Peralta, & Aparicio, 2015; Chu, Lin, Jang, & Chang, 2010; Contreras, Ballari, De Bruin, & Samaniego, 2019; Domenech, Castro‐Franco, Costa, & Amiotti, 2017; Schmidt et al, 2014) concluded that cLHS in combination with kriging or random forest for mapping gave the most accurate prediction. These studies promote the use of cLHS as an effective sampling design for mapping.…”
Section: Discussionmentioning
confidence: 99%
“…In our case studies, SRS and cLHS were equivalent in terms of map accuracy. Several studies (e.g., Castro‐Franco, Costa, Peralta, & Aparicio, 2015; Chu, Lin, Jang, & Chang, 2010; Contreras, Ballari, De Bruin, & Samaniego, 2019; Domenech, Castro‐Franco, Costa, & Amiotti, 2017; Schmidt et al, 2014) concluded that cLHS in combination with kriging or random forest for mapping gave the most accurate prediction. These studies promote the use of cLHS as an effective sampling design for mapping.…”
Section: Discussionmentioning
confidence: 99%
“…ECa measurements were collected on September 9th, 2016 using a Veris® 3100 soil electrical conductivity sensor (Veris Technologies Inc., Salina, KS, USA). With this sensor, the system records ECa in mS m −1 by electrical resistivity at a shallow depth (0 to 30 cm, ECa 0-30 cm) and deep depth (0 to 90, ECa 0-90 cm) (Castro Franco et al, 2015). ECa measurements were made along parallel transects approximately 20 m apart on the surface of the experimental site.…”
Section: Delimitation Of Soil-specific Zonesmentioning
confidence: 99%
“…Techniques to estimate optimal sample size are critical to supporting soil management, crop productivity, and environmental conservation. Several applications include the prediction of crop yields [8,9], spatial variability of soil properties at the farm scale [10,11], and precision agriculture prescriptions [12,13] in agricultural systems. Sample size plays a critical role in predictive modeling of aboveground biomass and species distribution in forest systems [14,15] and in the calibration of models to predict soil properties from spectroscopy data [16,17] in soil science.…”
Section: Introductionmentioning
confidence: 99%